ANALISIS MANAJEMEN LABA DI SEKITAR (SEBELUM, SAAT DAN SESUDAH) PENERBITAN OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA (BEJ) - Risa Watti (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2006)
The purpose of this research is to obtain the empirical evidence of the company which has already issued the obligation. Whether that such company issues the obligation manipulates its earnings (or conducting